(untitled) (Fiep Bulletin - online, 2011)
To study the physiological effect and biochemists generated for the training if they have presented as a latent necessity of the modern porting training. The Sanshou is the modality of combat of the Kung fu-wushu, where the regulation allows punch, kicks and fall. In the present study the amounts of creatine kinase had been measure (CK) in rest and immediately after a session of training of sanshou under the approach of the combat. A 20 individuals of the masculine sort had participated of this study, chosen of random form between the athletes sanshou with at least one year of experience in competitions, with register in the Association International Chan Lee kung fu-RIO DE JANEIRO, tied with the Federacy of Kung fu of the State of Rio De Janeiro, with age of 22.42 ± 4,4 years (MEDIUN ± SD), weight 67,07 ± 8,6 kg, stature 170,7 ± 5,3 cm and percentage of 10.42 fat of ± 3,3, healthful ones, that they had not presented no type of injury or opportunist illness for at least one month before the experimental protocol. Statistical the considered level of significance was of p < 0,05. The CK concentrations had presented, an increase of approximately 38% demonstrating that the training of sanshou is of great intensity causing muscular damages modifying the permeability of the membrane of muscular staple fibres.